Glutamate receptors of the A5 region modulate cardiovascular responses evoked from the dorsomedial hypothalamic nucleus and perifornical area - López-González, Manuel Víctor; Díaz-Casares, Amelia; González-García, Marta; Peinado-Aragonés, Carlos Antonio; Barbancho-Fernández, Miguel Ángel; Carrillo-de-Albornoz, Margarita; Dawid-Milner, Marc Stefan (Springer, 2018)
To assess the possible function of glutamate in the interaction between the dorsomedial hypothalamic nucleus-perifornical area (DMH-PeF) and the A5 pontine region (A5), cardiovascular and respiratory changes were studied in response to electrical stimulation of the DMH-PeF (1 ms pulses, 30–50 μA given at 100 Hz for 5 s) before and after the microinjection of kynurenic acid (non-specific glutamate receptor antagonist; 50 nl, 5 nmol), MK-801 (NMDA receptor antagonist; 50 nl, 50 nmol), CNQX (non-NMDA receptor antagonist; 50 nl, 50 nmol) or MCPG (metabotropic glutamate receptor antagonist; 50 nl, 5 nmol) within the A5 region. DMH-PeF electrical stimulation elicited a pressor (p < 0.001) and tachycardic response (p < 0.001) which was accompanied by an inspiratory facilitation characterised by an increase in respiratory rate (p < 0.001) due to a decrease in expiratory time (p < 0.01). Kynurenic acid within the A5 region decreased the tachycardia (p < 0.001) and the intensity of the blood pressure response (p < 0.001) to DMH-PeF stimulation. After the microinjection of MK-801 and CNQX into the A5 region, the magnitude of the tachycardia and the pressor response were decreased (p < 0.05 and p < 0.01; p < 0.001 and p < 0.05, respectively). After MCPG microinjection into the A5 region, a decrease in the tachycardia (p < 0.001) with no changes in the pressor response was observed during DMH-PeF stimulation. The respiratory response elicited by DMH-PeF stimulation was not changed after the microinjection of kynurenic acid, MK-801, CNQX or MCPG within the A5 region. These results suggest that A5 region glutamate receptors play a role in the cardiovascular response elicited from the DMH-PeF. The possible mechanisms involved in these interactions are discussed.
Keywords: Respiración - Regulación - Modelos animales; Corazón - Regulación - Modelos animales; Experimentación animal; A5 Region; Glutamate; Dorsomedial Hypothalamic Nuecleus; Respiratory Control; Cardiovascular Control; Rat